Keefektifan Media Digital dalam Pembelajaran Aksara Sunda - Ridwan, Fajar Mohamad; Nugraha, Haris Santosa (Yayasan Indonesia Bermutu, 2024)
Sundanese script is an ancient Sundanese scriptwhose writing system has been standardized inaccordance with the development of Sundaneselanguage used by Sundanese people today. Along withthe development of the digital era, of course itinfluences learning in schools, especially Sundanesescript. Therefore, it is necessary to pay attention towhether learning Sundanese script using digital mediais effective or not? Then the method used in thisresearch is Systematic Literature Review (SLR), whichis also called literature study, namely by reviewingprevious research within the last 10 years. There are20 articles about learning Sundanese script usingdigital media using the PICOS approach. The studydiscovered that digital media packed as beautifully aspossible helps in introducing, training, and becomingaccustomed to using Sundanese script.